2013
DOI: 10.1186/1747-597x-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Do parent–child acculturation gaps affect early adolescent Latino alcohol use? A study of the probability and extent of use

Abstract: The literature has been mixed regarding how parent–child relationships are affected by the acculturation process and how this process relates to alcohol use among Latino youth. The mixed results may be due to, at least, two factors: First, staggered migration in which one or both parents arrive to the new country and then send for the children may lead to faster acculturation in parents than in children for some families. Second, acculturation may have different effects depending on which aspects of alcohol us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…For example, recent data have found a significant reduction in non-medical POA use in the general Ontario adult population, which may be related to recent reductions in overall POA availability [54]. At the same time, we note the observed key changes in POA dispensing levels occurred prior to the launch of a Canadian ‘National Prescription Drug Use Strategy’ – a package of recommendations and measures aimed at the prevention, surveillance, treatment and enforcement of POA-related problems assembled by various governmental agencies and non-governmental stakeholders – in 2013 [55].…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent data have found a significant reduction in non-medical POA use in the general Ontario adult population, which may be related to recent reductions in overall POA availability [54]. At the same time, we note the observed key changes in POA dispensing levels occurred prior to the launch of a Canadian ‘National Prescription Drug Use Strategy’ – a package of recommendations and measures aimed at the prevention, surveillance, treatment and enforcement of POA-related problems assembled by various governmental agencies and non-governmental stakeholders – in 2013 [55].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Spanish-language discrepancies might be more consequential for the parent-child relationship than English-language discrepancies. Yet, Spanish-language proficiency and preference have not been widely examined in studies of parent-child cultural discrepancies; they mostly have used differences in English-language use as indicators of cultural discrepancies (e.g., Cox et al, 2013;Pasch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Various types of parent-child acculturation gaps have been identified (for a review, see Telzer, 2011). The most common gaps occur when U.S.-reared children embrace the country's culture to a higher degree than the parents' heritage culture, while their parents adhere to their heritage culture to a higher degree than the U.S. culture (Bámaca-Colbert & Gayles, 2010;Cox, Zapata Roblyer, Merten, Shreffler, & Schwerdtfeger, 2013;Smokowski, Rose, & Bacallao, 2008 Although it is well established that Latino children tend to acculturate to the U.S. culture at a faster pace than their parents, a purported association between parent-child acculturation gaps and parent-child conflict among Latino families is still being debated (see Telzer, 2011). For example, using quantitative methods, Bámaca-Colbert, Umaña-Taylor, and Gayles (2012) found that mother-daughter acculturation gaps were associated with mother-daughter conflict among Mexican American middle adolescents, but not early adolescents.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%
“…The acculturation gap hypothesis is complex as not all immigrant families are impacted by parent–youth cultural gaps in similar ways and acculturation gaps can have multiple manifestations (Cox, Zapata Roblyer, Merten, Shreffler, & Schwerdtfeger, 2013; Telzer, 2011). However, prevention studies also indicate that parenting interventions for Latino/a immigrant families with a focus on biculturalism can increase family cohesion, improve parenting practices, and reduce parent–youth conflict (Smokowski et al, 2009).…”
Section: Scope Of the Studymentioning
confidence: 99%